Chitosan-based delivery system enhances antimicrobial activity of chlorhexidine - Hemmingsen, Lisa Myrseth; Panchai, Pimmat; Julin, Kjersti; Basnet, Purusotam; Nystad, Mona; Johannessen, Mona; Škalko-Basnet, Nataša (Frontiers in Microbiology, 2022)
Skin infections and infected chronic skin wounds are increasingly putting pressure on the health care providers and patients. The pressure is especially concerning due to the rise of antimicrobial resistance and biofilm-producing bacteria that further impair treatment success. Therefore, innovative strategies for wound healing and bacterial eradication are urgently needed; utilization of materials with inherent biological properties could offer a potential solution. Chitosan is one of the most frequently used polymers in drug dosage forms and delivery systems. This bioactive polymer is often regarded as an attractive constituent in delivery systems due to its inherent antimicrobial, anti-inflammatory, anti-oxidative and wound healing properties. However, lipid-based vesicles and liposomes are generally considered more suitable as delivery systems for skin and skin wounds due to their ability to interact with the skin structure and provide prolonged release, protect the antimicrobial compound, and allow high local concentrations at the infected site. To take advantage of the beneficial attributes of both the lipid-based vesicles and chitosan, these components can be combined into chitosan-containing liposomes or chitosomes and chitosan-coated liposomes. In this study, we aimed to investigate whether both the chitosan-containing liposomes and chitosan-coated liposomes could improve the antimicrobial activity of the membrane-active antimicrobial chlorhexidine, while assuring both the anti-inflammatory activity and cell viability. Chlorhexidine was incorporated into three different vesicles, namely plain (chitosan-free), chitosan-containing and chitosan-coated liposomes that were optimized for skin wounds. Their antimicrobial activities, anti-inflammatory properties, and cell compatibility were assessed in vitro. The vesicles comprising chitosan demonstrated slower release rate of chlorhexidine and high cell compatibility. Additionally, the inflammatory responses in murine macrophages treated with these vesicles were reduced by about 60% compared to non-treated cells. Finally, liposomes containing both chitosan and chlorhexidine demonstrated the strongest antimicrobial effect against Staphylococcus aureus. Both chitosan-containing and chitosan-coated liposomes comprising chitosan could serve as an excellent platform for the delivery of membrane-active antimicrobials to infected wounds.